ONTWIKKELINGSBEHOEFTES EN ADMINISTRASIE - De Beer, F. (Scientia Militaria - South African Journal of Military Studies, 2012)
With a colonial history of paternalistic administration behind it, the Third World burocracies have suddenly been given the task to playa development role apart from their administrative functions. In several countries (inter alia Malawi, Botswana and Swaziland) variations in development committees and boards have been experimented with, with a varying degree of success. The ideal Institution for interaction between government and population must yet be created and will probably differ from country to country. A ’development administration-doctrine’ is coming into being, but many shortcomings must still be dealt with before an ideal approach will emerge.